Information management and population behavior in social isolation during COVID 19 - Pulido-Capurro, Victor (2021)
Objective: Explain some of the causes that have influenced the little success achieved by social isolation, which has not allowed to mitigate the effects of the COVID-19 pandemic. Methods. To find out some of the causes, a survey was applied virtually, between June 12 and 22, 2020, to 568 people segmented into three age groups: A from 17 to 35 years old, B from 36 to 54 years old and C from 55 to 71 years. Although the survey consisted of a 29-question questionnaire, for the present work only five questions related to social isolation have been taken into consideration. Results. A slightly greater interest in being informed is evidenced in the C age range, the most used medium for information is television (86%) in the C range and social networks (52%) for the A range, these also being the ones that more are reported through official channels (58%). For most age groups (39%) it creates confusion that the level of non-compliance with quarantine and distancing to prevent COVID-19 is due to information. Conclusions. The dissemination of false news constitutes a threat to society, especially in these times of pandemic since it deliberately directs towards an erroneous interpretation of the facts in such a way that the falsehood is disguised as the truth, undermining the success of social isolation.